Role of Living Conditions and Socioenvironmental Factors on Chronotype in Adolescents - Prasun Haldar; Smriti Debnath; Ana Adan; Konrad S. Jankowski; Dwiptirtha Chattopadhyay; Santi Gopal Maity; Saibal Moitra; Paige Lacy; Subhabrata Moitra (MDPI AG, 2021)
An individual's chronotype, defined as the preference for rest and activity at different times of the day, is linked to several physiological and psychological outcomes. Research on environmental determinants of chronotype has focussed mostly on geographic location, whereas other socioenvironmental determinants have been neglected. We aimed to investigate the association between other previously unrecognized socioenvironmental factors and chronotypes in adolescents. We analysed data of 1916 Bengali adolescents (aged between 13-14 years, 47% girls). Chronotype was determined by the reduced morningness-eveningness questionnaire (rMEQ), and socioenvironmental factors were identified through a structured questionnaire. Associations were analysed using multinomial logistic regression models. Our findings demonstrated that living in urban areas, the presence of a smoker at home, and higher parental education were associated with a higher evening activity (eveningness), while the use of biomass cooking media (compared to liquefied petroleum gas) and assisting parents in farming were associated with higher morningness in adolescents. This is the first study to identify the association between previously unrecognized socioenvironmental factors and chronotypes delineating the interaction between environment and sleep in adolescents and might help the parents to understand the importance of a proper sleep-activity rhythm of their kids through a comprehensive understanding of their surrounding environment and other factors.